Variable-frequency lock-in detection for the suppression of beat noise in Brillouin optical correlation domain analysis - Jeong, Ji Ho; Lee, Kwanil; Song, Kwang Yong; Jeong, Je-Myung; Lee, Sang Bae (OPTICAL SOC AMER, 2011)
We propose and experimentally demonstrate a novel lock-in detection method to avoid a beat noise in Brillouin optical correlation domain analysis (BOCDA) which appears in the sweep of the sensing position and deteriorates the measurement accuracy by distorting the acquired Brillouin gain spectrum. In our analysis, the origin of the beat noise is shown to be the fluctuation of the Brillouin gain induced by the chopping of the intensity-modulated pump wave, and the optimal relation between the modulation and the lock-in frequencies is developed as an effective solution to circumvent the beat noise. (C) 2011 Optical Society of America
Keywords: DISTRIBUTED FIBER SENSOR; STRAIN-MEASUREMENT; BOTDA; MODULATION; PROPOSAL; RANGE